The less-than-hidden secrets and final revelations of Lydia Goldblatt & Julie Graham-Chang - Ignatow, Amy (New York : Amulet Books, 2014)
Lydia and Julie's comparative peace is shattered when Hamlin Junior High plays host to new students whose school has burned down, a situation that culminates in a heated rivalry and a dance battle.
Keywords: Best friends -- Juvenile fiction; Fiction